(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to compare the clinical and laboratory characteristics between albuminuric diabetic kidney disease and non-albuminuric diabetic kidney disease phenotypes. Subjects and methods: A cross-sectional study was conducted on 181 patients with type 2 diabetes mellitus (eGFR < 60 mL/min/1.73 m²) at the University Medical Center Ho Chi Minh City - Campus 2. Evaluation parameters included clinical characteristics, lipid profiles, eGFR, UACR, homocysteine levels, the systemic immune-inflammation index (SII), and the prognostic nutritional index (PNI). Results: The ratio of business ownership accounted for 35%. The albuminuric diabetic kidney disease group had a lower mean age (65.2 vs 67.9 years, p = 0.0401), women were predominant (64.4% vs 47.6%, p = 0.029), and blood pressure was less controlled (systolic blood pressure 144.6 vs 134.9 mmHg, p = 0.011). The NADKD group had a better eGFR (43.7 mL/min/1.73 m² vs 33.6 mL/min/1.73 m², p < 0,001), higher blood albumin (4.3 g/dL vs 4.1 g/dL, p = 0.0002), lower SII (464.6 vs 574.2, p = 0.0145), and higher PNI (56.5 vs 53.1, p = 0.0001). There was no difference in BMI, diabetes time, blood glucose control (fasting blood glucose, HbA1c), and homocysteine between the two groups. Conclusions: Diabetic kidney disease manifests through multiple phenotypes with distinct biological, inflammatory, and nutritional profiles. Relying solely on UACR is insufficient for adequate screening and risk stratification. The SII and PNI indices serve as potential biomarkers for phenotypic identification and may guide individualized management strategies in clinical practice.